Ochratoxin A removal in synthetic media by living and heat-inactivated cells of Oenococcus oeni isolated from wines - Mateo, Eva M.; Medina, Angel; Mateo, Fernando; Valle-Algarra, Francisco M.; Pardo, Isabel; Jimenez, Misericordia (Elsevier, 2010)
The capacity of Oenococcus oeni to eliminate ochratoxin A (OTA) from synthetic media in different conditions was studied. Ten tested O. oeni strains removed OTA from the medium but with significant differences depending on the strain, incubation period, and initial OTA level in the medium. Mycotoxin reductions higher than 60% were recorded in 14-day cultures spiked with 2 mu g OTA/l. Toxin removal was independent of bacterial viability and culture medium composition. This is the first study carried out to study OTA removal dynamics by living and heat-inactivated cells of O. oeni. The results aim that this bacterium may be a very useful tool to control OTA in food and beverages. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Ochratoxin A removal; Oenococcus oeni; Food safety